Role of pannexins in vasculature - Habib, Alaa (2017)
Pannexins are newly discovered proteins that were first discovered by Panchin in 2000. The pannexin family has three isomers, i.e. pannexin-1, pannexin-2, and pannexin-3. In 2011, Billaud et al suggested that pannexin1 channels contribute to the spread of vasoconstriction after activation of α1D-adrenoceptors present on the surface of vascular smooth muscle cell (VSMCs) of thoracodorsal resistance arteries (TDA) isolated from mice. Phenylephrine acting upon the α1D-adrenoceptors activated pannexin1 channels present in the cell to release ATP, which in turn activated P2Y receptors on neighbouring cells to produce a co-ordinated contractile response. This aim of this work was to further investigate the role of pannexin in the regulation of contractile responses in the vasculature. To this end, the present study examined the presence and function of pannexins in the porcine splenic artery (PSA) and the rat aorta (RA), in which α1A- and α1D-adrenoceptors are present respectively. The role of pannexin channels and ATP (via activation of P2 purinoceptors) in the response to exogenous NA-induced contractile responses in the PSA and the RA were investigated, as were responses to sympathetic nerve activation in the PSA. The involvement of pannexin channels was studied using several pannexin inhibitors, i.e. mefloquine (a non-selective pannexin inhibitor), probenecid (a selective pannexin1 inhibitor at low concentrations), carbenoxolone (a selective pannexin1 inhibitor) and Brilliant Blue FCF (a selective pannexin1 inhibitor). Additionally, the involvement of ATP in NA-induced responses was examined using P2 purinoceptor antagonists (PPADS, suramin and NF449). Further experiments examined the role of pannexins in contributing to endothelium-dependent responses in a large vessel i.e. the porcine coronary artery (PCA).